Cracking Driving Force at the Tip of SCC under Heterogeneous Material Mechanics Model of Safe-End Dissimilar Metal-Welded Joints in PWR - Yuman Sun; He Xue; Kuan Zhao; Yubiao Zhang; Youjun Zhao; Weiming Yan; Rehmat Bashir (Science and Technology of Nuclear Installations)
The complicated driving force at the stress corrosion cracking (SCC) tip of the safe-end dissimilar metal-welded joints (DMWJs) in the pressurized water reactor (PWR) is mainly caused by the heterogeneous material mechanical properties. In this research, to accurately evaluate the crack driving force at the SCC in DMWJs, the stress-strain condition, stress triaxiality, and J-integral of the crack tip at different positions are analyzed based on the heterogeneous material properties model. The results indicate that the larger driving force will be provided for the I-type crack when the crack is in the SA508 zone and the interface between the 316L region and base metal. In addition, the heterogeneous material properties inhibit the J-integral of the crack in the 316L region, which has a promoting effect when the crack is in the SA508 zone and weld metal. It provides a new idea for analyzing driving force at the crack tip and safety evaluation of DMWJs in PWRs.